Immunogenicity of SEREX-identified antigens and disease outcome in pancreatic cancer - Heller, Anette; Zörnig, Inka; Müller, T.; Giorgadze, K.; Frei, Claudia; Giese, Thomas; Bergmann, Frank; Schmidt, Jan; Werner, Jens; Büchler, Markus W.; Jäger, Dirk; Giese, Nathalia (Cancer immunology immunotherapy, 2010)
Despite spontaneous or vaccination-induced immune responses, pancreatic cancer remains one of the most deadly immunotherapy-resistant malignancies. We sought to comprehend the spectrum of pancreatic tumor-associated antigens (pTAAs) and to assess the clinical relevance of their immunogenicity. An autologous SEREX-based screening of a cDNA library constructed from a pancreatic T3N0M0/GIII specimen belonging to a long-term survivor (36 months) revealed 18 immunogenic pTAA. RT-PCR analysis displayed broad distribution of the identified antigens among normal human tissues. PNLIPRP2 and MIA demonstrated the most distinct pancreatic cancer-specific patterns. ELISA-based screening of sera for corresponding autoantibodies revealed that although significantly increased, the immunogenicity of these molecules was not a common feature in pancreatic cancer. QRT-PCR and immunohistochemistry characterized PNLIPRP2 as a robust acinar cell-specific marker whose decreased expression mirrored the disappearance of parenchyma in the diseased organ, but was not related to the presence of PNLIPRP2 autoantibodies. Analyses of MIA—known to be preferentially expressed in malignant cells—surprisingly revealed an inverse correlation between intratumoral gene expression and the emergence of autoantibodies. MIAhigh patients were autoantibody-negative and had shorter median survival when compared with autoantibody-positive MIAlow patients (12 vs. 34 months). The observed pTAA spectrum comprised molecules associated with acinar, stromal and malignant structures, thus presenting novel targets for tumor cell-specific therapies as well as for approaches based on the bystander effects. Applying the concept of cancer immunoediting to interpret relationships between gene expression, antitumor immune responses, and clinical outcome might better discriminate between past and ongoing immune responses, consequently enabling prognostic stratification of patients and individual adjustment of immunotherapy.